EPIDEMIOLOGICAL TRENDS AND CURRENT STATE OF THE PROBLEM OF MULTIDRUG-RESISTANT TUBERCULOSIS IN ZAKARPATTIA OBLAST - Коваль, Галина; Височанська, Власта (SWorldJournal, 2025)
The aim of this study was to summarize the current epidemiological status of multidrug-resistant tuberculosis (MDR-TB) in the Zakarpattia region, analyze trends over recent years, and identify key risk factors influencing the spread of resistant forms of